Intra‐articular delivery of glucosamine for treatment of experimental osteoarthritis created by a medial meniscectomy in a rat model. Issue 2 (5th November 2013) - Gibson, Matthew; Li, Hanwei; Coburn, Jeannine; Moroni, Lorenzo; Nahas, Zayna; Bingham, Clifford; Yarema, Kevin; Elisseeff, Jennifer
ABSTRACT Glucosamine (GlcN) is a naturally occurring amino‐monosaccharide with putative chondroprotective activity. Optimum responses to GlcN are achieved at concentrations which are impractical with oral dosing. Intra‐articular delivery of a bolus dose of GlcN is one way to overcome these pharmacokinetic obstacles. In this study we report the effects of exposing primary human chondrocytes to a bolus dose of GlcN. We also locally administered GlcN in the context of a meniscal transection model of rat osteoarthritis (OA). The knees of male rats were subjected to medial meniscal transection and developed arthritic changes over 4 weeks. Treatment groups were then given thrice weekly 100 μL injections of 35 μg, 350 μg, 1.8 mg, or 3.5 mg of GlcN dissolved in normal saline. Gross images, modified Mankin scores, and histomorphometric measurements were used as outcome measures. The 350 μg dosage of GlcN had the most significant positive impact on all components of the modified Mankin score. Together, these findings suggest the local delivery of high concentrations of GlcN is well tolerated and can suppress experimental OA through influences on both bone and cartilage. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:302–309, 2014.